Implementation of Delayed Umbilical Cord Clamping Guideline for a Labor & Delivery Unit [36B]. (May 2018) - Williams, Nayo; Townsel, Courtney; Assad, Maushumi; Johnson, Kendall; Campbell, Winston; Sink, David
Abstract : INTRODUCTION: Delayed cord clamping (DCC) allows for placental transfusion and has proven benefits. Our institution's delivery unit and Neonatal Intensive Care Unit (NICU) had no guideline for DCC despite good evidence for the practice since 2012. Working as a multi-disciplinary team, our aim was to develop, implement and monitor with quality improvement (QI) review a DCC guideline initiated in January 2017. METHODS: The guideline was drafted during inter-divisional perinatal-neonatal conferences using the Plan-Do-Study-Act model. The guideline included umbilical cord milking (UCM) as an option for placental transfusion. A department-wide email was sent to obstetrical and neonatal providers, as well as information sessions for the labor unit and NICU nursing staff explaining the new guideline, and exclusion criteria (unconfirmed dichorionic gestation, abruption and immediate resuscitation/stabilization of neonate and/or mother). Obstetrical residents documented whether DCC/UCM was performed. Our target was 80% of all neonates to undergo DCC/UCM. Descriptive statistics and chi-square test were utilized; P < .05 was significant. RESULTS: January through August 2017, 500 neonates delivered and 84.3%, of eligible neonates (408/484) underwent DCC/UCM (when DCC/UCM was not documented, we assumed it wasn't performed). The rate increased over time, ranging from 63.5% to 98.3%. There was no statistical difference in DCC/UCM rates by preterm vs term (P=.70) or delivery route (P=.62). CONCLUSION: We reached our goal 80% of neonates undergoing DCC/UCM one month after initiation of the guideline. The QI review identified that documentation, communication, length of stay and hyperbilirubinemia rates are important areas for improvement and should be reevaluated with the next Plan-Do-Study-Act cycle.